Respiratory Constraints in Verbal and Non-verbal Communication - Włodarczak, Marcin; Heldner, Mattias (Frontiers in Psychology, 2017)
In the present paper we address the old question of respiratory planning in speech production. We recast the problem in terms of speakers’ communicative goals and propose that speakers try to minimise respiratory effort in line with H&H theory. We analyze respiratory cycles coinciding with no speech (i.e. silence), short verbal feedback expressions (SFE’s) as well as longer vocalisations in terms of parameters of the respiratory cycle and find little evidence for respiratory planning in feedback production. We also investigate timing of speech and SFEs in the exhalation and contrast it with nods. We find that while speech is strongly tied to the exhalation onset, SFEs are distributed much more uniformly throughout the exhalation and are often produced on residual air. Given that nods, which do not have any respiratory constraints, tend to be more frequent towards the end of an exhalation, we propose a mechanism whereby respiratory patterns are determined by the trade-off between speakers’ communicative goals and respiratory constraints.